Modeling the Application of IHE QRPH Profiles in Data Integration Centers: A Practical Approach with 3LGM2. - Draeger, C.; Staubert, S.; Kuntz, A.; Henke, C.; Winter, A.; Sax, U.; Lobe, M. (Stud Health Technol Inform, 2023)
The Data Integration Centers (DICs), all part of the German Medical Informatics Initiative (MII), prepare routine care data captured in university hospitals to enable its reuse in clinical research. Tackling this challenging task requires them to maintain multiple data stores, implement the necessary transformation processes, and provide the required terminology services, all while also addressing the use case specific needs researchers might have. An MII wide application of the standardized profiles defined in the IHE QRPH domain might therefore be able to drastically reduce the overhead at any one DIC. The MII DIC reference model built in 3LGM2, a method to describe complex information system architectures, serves as a starting point to evaluate whether such an application is possible. We first extend the IHE modeling capabilities of 3LGM2 to also support the five profiles from the QRPH domain that our experts evaluated as relevant in the MII DIC context. We then expand the DIC reference model by some IHE QRPH actors and transactions, showing that their application could be beneficial in the MII DIC context, provided they surpass their trial status.
Keywords: Humans; Systems Integration; *Medical Informatics Applications; *Medical Informatics